Programa para diagnóstico molecular de hemofilia A y B en Colombia. - Yunis Hazbun, Luz Karime; Parrado Jara, Yolima; Linares Ballesteros, Adriana; Yunis Londoño, Juan José (Revista Colombiana de Hematología y Oncología, 2018)
.